Building Entrepreneurial Spirit through Saturday Canteen Activities at Elementary School - Rr. Agustien Lilawati (EDUTEC : Journal of Education And Technology, 2023)
Entrepreneurial spirit encompasses self-reliance in seeking income through business ventures or channeling personal creativity into income-generating opportunities. Entrepreneurship education, however, goes beyond teaching children the basics of business; it aims to develop their mental and character traits. A study conducted at RA Dwi Savitri in Surabaya sought to describe the cultivation of entrepreneurial spirit through the Saturday Canteen activity. Data was gathered through interviews, observations, and documentation, and analyzed descriptively. The results showed that the Saturday Canteen activity serves as a training ground for entrepreneurship. The school facilitates this activity by scheduling it every Saturday, with 3-4 students acting as sellers and handling real monetary transactions. This experience instills traits such as creativity, responsibility, honesty, trustworthiness, independence, and self-confidence. Teachers also play a role in monitoring and guiding students during the Saturday Canteen activity, ensuring its effectiveness in fostering entrepreneurial skills and mindset.